Unraveling agricultural water pollution despite an ecological policy in the Ayeyarwady Basin - Lazarus Obed Livingstone Banda; Chigonjetso Victoria Banda; Jane Thokozani Banda; Eretia Mwaene; George N. Chidimbah Munthali; Thin Thin Hlaing; Blessings Chiwosi (BMC, 2024)
Abstract Background The Ayeyarwady Basin in Myanmar, a critical economic zone, faces severe ecological degradation due to unsustainable agricultural practices. These practices pose significant threats to human health and marine biodiversity. Environmental threats persist despite the Myanmar government's efforts to implement biodiversity protection policies. This research explores the limited compliance with environmental protection policies among farmers in the Ayeyarwady Basin and its implications for sustainable agricultural practices and ecological conservation. Methods This research employs an exploratory phenomenological approach, utilizing semi-structured, in-depth interviews with government officials and farmers (N = 30). The data collected were subjected to thematic analysis using Atlas 23. Results Preliminary findings reveal a gap in farmers' awareness and understanding of these policies, hindered by insufficient financing, poor communication infrastructure, and uncoordinated policy monitoring. These factors and existing unrest contribute to a top-down policy approach that neglects frontline stakeholders. The study suggests the need for clear stakeholder roles, adequate policy financing, and diverse communication strategies to effectively implement environmental policies and protect human and marine life. Conclusions Environmental policy shortcomings in Myanmar are attributable to governmental oversight and insufficient stakeholder engagement. To mitigate pollution and safeguard river basin ecosystems, the government must delineate stakeholder responsibilities, allocate appropriate policy funding, and adopt varied communication approaches with farmers. Graphical Abstract